Loading device of explosive stress wave in high confining pressure and dynamic response of composite structure. (15th February 2021) - Liu, Chenkang; Yue, Songlin; Wang, Mingyang; Li, Jie; Deng, Shuxin; Zhang, Guokai; Ji, Yuguo; Li, Zhihao; Xu, Tianhan
Abstract: This paper presents an equivalent loading device of explosive stress wave to investigate the propagation law of stress wave in high-geo-stress rock mass under explosive disturbance. The loading device was used to simulate the propagation law of explosion stress wave in water and composite structure under high confining pressure. The device can generate plane stress waves, and the stress waveforms measured by sensors arranged on the same plane have good consistency. According to the time sequence relationship of the stress curve, the propagation law of the stress wave between layers was obtained, and the stress wave has no obvious attenuation. Within a certain hydrostatic pressure range, with the increase of pressure, the peak value of the stress wave showed an upward trend, while there was little change in positive pressure holding time. The successful development of the stress wave equivalent loading device makes the explosive disturbance loading under high ground stress safe and controllable. It is a new type of deep geomechanical test method.